Fumonisin and T-2 toxin production of Fusarium spp. isolated from complete feed and individual agricultural commodities used in shrimp farming - Anukul,N. (Springer-Verlag GmbH and Co. KG, 2015)
Fusarium spp. are plant pathogens producing fumonisins and trichothecenes that both affect human and animal health. In the present study, 40 fungal strains were isolated and species identified from 35 shrimp feed samples and from 61 agricultural raw materials. F. verticillioides was the predominant species (85 %) mostly found in corn and soybean meal, while no Fusarium contamination was detected in shrimp feed. Levels of 10 % of F. oxysporum were isolated from peanut and 5 % of F. equiseti contamination in corn and peanut. To determine the ability of toxin production, enzyme-linked immunosorbent assay, polymerase chain reaction, and ultra-pressure liquid chromatography-tandem mass spectrometry were performed. All but four of the fumonisin-producing strains contained the FUM1 gene. No Fusarium synthesized T-2 toxin nor contained the Tri5 gene. This survey brings more data on mycotoxin contamination in the food chain of animal feed production, and leads to the awareness of the use of contaminated raw materials in shrimp farming. © 2013 Society for Mycotoxin Research and Springer-Verlag Berlin Heidelberg.